2011 Developments in E-Systems Engineering 2011
DOI: 10.1109/dese.2011.79
|View full text |Cite
|
Sign up to set email alerts
|

MoHTAM: A Technology Acceptance Model for Mobile Health Applications

Abstract: In spite of the advancement and variety of available mobile based applications, there is an eminent need to investigate the current position of the acceptance of those mobile health applications that are tailored towards the patients' medical information management and access. This paper explores and analysis the technology acceptance of the use of smart mobile phones from users' perceptions, viewpoint, and experience. The paper will focus on studies of the factors affecting the intention to use the smart mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 7 publications
4
35
0
1
Order By: Relevance
“…Also, this study empirically shows that PEOU is significantly correlated with PU (H3: β=0.409, p<0.001). This result conforms with prior findings (Mohamed, 2011;Wu et al, 2011;Hung and Jen, 2012;Xue et al, 2012). The current result implies that if the individuals feel that the m-healthcare is easy to use and effortless to manage they will tend to perceive it as useful.…”
Section: Wwwccsenetorg/ibrsupporting
confidence: 91%
See 3 more Smart Citations
“…Also, this study empirically shows that PEOU is significantly correlated with PU (H3: β=0.409, p<0.001). This result conforms with prior findings (Mohamed, 2011;Wu et al, 2011;Hung and Jen, 2012;Xue et al, 2012). The current result implies that if the individuals feel that the m-healthcare is easy to use and effortless to manage they will tend to perceive it as useful.…”
Section: Wwwccsenetorg/ibrsupporting
confidence: 91%
“…8, No. 9; Similar findings were reported by information technology adoption studies implemented in the context of different healthcare domains (Lin, 2011;Mohamed, 2011;Hung & Jen, 2012;Xue et al, 2012;Jaradat & Smadi, 2013;Kuo et al, 2013). In fact, the strength of PU and BI relationship is obviously comparable to prior studies in the field, however the strength of the relationship between PEOU and BI is much stronger than what concluded by previous studies.…”
Section: Wwwccsenetorg/ibrsupporting
confidence: 78%
See 2 more Smart Citations
“…Three identified features of TPB mainly focused on investigating beliefs related to each situation, beliefs that may generalize to other situations and other beliefs that may not [12]. The combined TAM and TPB (C-TAM-TPB) developed by [23] as a hybrid model integrated to include perceived behavioral control and subjective norms into the TAM demonstrated thru empirical study that revealed results of high corresponding in describing the behaviors of users on using new technology [13]. The Decomposed Theory of Planned Behavior (DTPB) was developed by [23] with the aims on explaining the users' behaviors based on the relationship between intention, attitude, behavior and beliefs.…”
Section: Literature Reviewmentioning
confidence: 99%